THE COMPARISON OF DIARRHEA INCIDENCE BETWEEN 0-6 MONTHS OLD INFANTS WHO WERE EXCLUSIVELY BREASTFED, NON-EXCLUSIVELY BREASTFED AND GIVEN MILK FORMULA IN CIREBON CITY, INDONESIA - Sukmawati, Dewi; Pratiwi, Witri; Malvi, Ahmad Fariz (Proceedings of the International Conference on Applied Science and Health, 2019)
Background: Infant diarrhea is one of the major health issues in Indonesia due to its high incidence and mortality. In 2015, the mortality rate of diarrhea and gastroenteritis in infants under one year in hospitals in Cirebon was 21%. Inappropriate infant feeding practice is one of the risk factors of diarrhea in infants. WHO recommends that every infant should get exclusive breastfeeding during the first 6 months of life and continued breastfeeding until 24 months of age. The aim of this study is to find out the difference in diarrhea incidence between 0-6 months old infants who were exclusively breastfed, non-exclusively breastfed, and given infant milk formula.Methods: This was an observational study with cross-sectional design. A total of 89 infants aged 0-6 months old were recruited by purposive sampling. The primary data were obtained using questionnaires that were filled by the mother or caregiver of the infants. The data were analyzed using the Chi-Square test and Prevalence Ratio was calculated.Results: The Chi-Square test showed a significant difference in diarrhea incidence between 0-6 months old infants who were exclusively breastfed, non-exclusively breastfed and infant milk formula (p=0,028). Infants who were not breastfed have 4 times higher risk of diarrhea (PR=4.145; CI95%= 1.198-14.400) compared to infants who were breastfed. Infants who were not exclusively breastfed has 3 times higher risk of diarrhea incidence compared to the infants receiving exclusive breastfeeding (RP=3.286; CI95%=1.144-9.434)Conclusion: Proper breastfeeding practice can decrease diarrhea incidence in infants aged 0-6 months. Mothers should be encouraged to exclusively breastfeed her baby during the first 6 months of life.